Saistību dzēšanas procedūra fiziskās personas maksātnespējas procesā - Avotiņa, Ivanda (Latvijas Universitāte, 2011)
Saistību dzēšanas procedūra ir jauns institūts fiziskās personas maksātnespējas procesā, kas stājās spēkā 2010.gada 1.novembrī. Darbā tiek analizēta jaunā Maksātnespējas likuma saistību dzēšanas procedūra no praktiskās puses, autorei norādot konkrētus uzlabojumus, kādi būtu veicami tiesību aktos. Autore ir minimāli analizējusi ārvalstu pieredzi, jo uzskata, ka ne katra ārvalstu pieredze būtu pārņemama un tā ne vienmēr integrējas Latvijas tiesību sistēmā. Autores ieskatā esošais regulējums Maksātnespējas likumā ir optimāls, bet uzlabojams. Tā kā šāds tiesību institūts Latvijā ir spēkā tikai dažus mēnešus, tad praksē vēl neviena persona Latvijā nav pilnībā ar to saskārusies. Tādēļ šis darbs un tajā paustās atziņas lielā mērā ir jauninājums, kas ir maz aplūkots juridiskajā literatūrā.

The new Latvian Insolvency Law, which entered into force on November 1, 2010, provides for significant changes in natural person's insolvency process solutions. The liabilities' cancellation is a new procedure in the natural person's insolvency process, and its aim is both to shorten the natural person's insolvency process and provide the fullest possible satisfaction of creditors' demands. The paper analyzes the liabilities' cancellation procedure in the new Insolvency Law from the practical side, assesses the restrictions for applying of the liabilities' cancellation and evaluates the preferential arrangements for cancellation of liabilities laid out in the Insolvency Law in view of their compatibility with the principles of equality established by the Latvian Constitution. The paper also analyzes the concept of debtor's property, looks into the concept of debtor's property resulting from fiduciary transactions, evaluates the judicial practice in calculating administrative expenses and challenging marital contracts. The author suggests particular improvements that should be made in the legislation to amend the insolvency process. Since the Law on liabilities' cancellation procedure is in force in Latvia only for a few months, no one in Latvia has yet fully experienced the topic described in the paper: liabilities' cancellation procedure in the natural person's insolvency process. Therefore, this paper and its conclusions to a large extent is a new contribution to a topic that is underrepresented in the legal literature of cases where the debtor is unable to pay his/her debts.
The cancellation procedure of a natural person in insolvency proceedings
Keywords: Juridiskā zinātne